Utilization of Online Media During Work From Home in Learning at STAHN Mpu Kuturan Singaraja - I Ketut Sudarsana; I Nyoman Temon Astawa (Jurnal Penelitian Agama Hindu, 2022)
This study aimed to analyze the utilization of online media during work from home in learning at STAHN MPU Kuturan Singaraja. The emergence phenomenon of online media, such as Zoom, is used as a learning medium nowadays and considered an easy-to-use learning resource. The research type was qualitative research with quantitative data support. The instruments used in this study were various data collection tools, such as interview guides, recording devices, and field notes. Data collection techniques used include; (a) participatory observation, (b) interviews, (c) documentation studies, (d) literature. The data analysis technique used in this research was the qualitative data analysis technique. The results showed that lecturers used online media, such as Zoom Cloud Meeting, Google Meet, Google Classroom, Telegram, and WhatsApp. The use of online media in online learning does not necessarily run smoothly. There are constraints faced by both lecturers and students, such as unstable internet signals and providers in each region, data package costs, delivery of teaching materials, and human resources (HR) who are not yet technologically literate. There is a good impact in the use of e-learning media during the work from home period that students and lecturers feel under conditions and pressures to evolve in the advancement of the use of technology and communication. The bad impact is boredom among new students because they cannot feel the college atmosphere by meeting other students face to face.